Життя і творчість Миколи Вороного на тлі родинного оточення письменника - Починок, Л.; Осяк, С. (Слово і Час, 2018)
Постать одного з перших апологетів модерністської естетики Миколи Вороного досі є
“terra incognita” як для широкого кола читачів, так і для науковців. У статті почасти розкрито
окремі грані його письменницького таланту, що гартувався під тиском глобальних історичних
та мистецьких зрушень. Зокрема, у дослідженні окреслено життєве і творче середовище
М. Вороного, простежено можливі впливи родинного оточення на формування світогляду й
таланту письменника. The figure of one of the first Ukrainian apologists of modernist aesthetics Mykola Voronyi still remains
‘terra incognita’ for most readers and scholars. Due to his artistic talent and principal literary position
Voronyi may take a special place among other poets of the early Ukrainian modernism. This paper
offers an attempt to get a closer look at the figure of the artist, revealing some aspects of his private
life and creative work under the pressure of global historical and artistic shifts.
In order to better understand the writer himself, and consequently his creative heritage, one must turn
to his world, to the environment in which he was born and formed as a person and artist. In particular,
the paper traces possible influence of the family environment on the formation of Mykola Voronyi’s
worldview and the writer’s talent. Some memories of his world, his family and creative environment
were left by Voronyi in a rather extensive autobiographical essay.
This autobiography of Mykola Voronyi, which is quite well-known and often cited by the authors of
scholarly and popular publications, allows the researcher to trace the origin of key motives and mood
in the creative consciousness of the writer, outline his artistic credo and life principles. According
to autobiographical records, the closest family environment (grandfather, father and mother) had a
profound and multifaceted formative influence on the personality of the future poet-lyricist, cultural
and public figure Mykola Voronyi. Фигура одного из первых апологетов модернистской эстетики
Николая Вороного до сих пор остается “terra incognita” как
для широкого круга читателей, так и для ученых. В статье
отчасти раскрыто отдельные грани его писательского таланта,
который закалялся под давлением глобальных исторических
и художественных сдвигов. В частности, в исследовании
определяется жизненная и творческая среда Н. Вороного,
прослеживаются возможные влияния семейного окружения на
формирование мировоззрения и таланта писателя.